Celebrating first nations languages and language learning in Australian schools
1 online resource
Keywords: "This book introduces key underlying principles for teaching First Nations languages and language learners in schools across a range of contexts. It takes a comprehensive approach covering traditional languages, new languages and English. At a critical time for Indigenous languages across the globe, the United Nations Decade of Indigenous Languages (2022-2032) draws attention to the endangerment of these languages and advocates for the role of education to preserve and revitalise Indigenous languages. At the same time, many new language varieties spoken by Indigenous peoples often remain unrecognised in education systems, and their English language learning needs are left unaddressed. This book provides crucial information to enhance the reader's knowledge of these critical issues in language and education with a view to promote future action. The chapters showcase the advocacy, activism and allyship for First Nations languages and language learners undertaken by educators, education systems and researchers in Australia. With a practical focus, this book illustrates innovative and contemporary approaches to language learning for First Nations students; educators can use this text to guide and develop language learning approaches in their respective contexts. This is a foundational resource for both Indigenous and non-Indigenous teachers and aspiring teachers alike, and all education professionals who appreciate the fundamental importance of language in education"--